The greater journey [large type] : Americans in Paris, [1830-1900] - McCullough, David G. (Thorndike Press, 2011)
Relates the story of the American artists, writers, and doctors who traveled to Paris in the nineteenth century, fell in love with the city and its people, and changed America through what they learned there.